Flood resilience, amenity and biodiversity benefits of an historic urban pond. (17th February 2020) - Krivtsov, Vladimir; Birkinshaw, Steve; Arthur, Scott; Knott, David; Monfries, Ruth; Wilson, Kirsty; Christie, Derek; Chamberlain, David; Brownless, Peter; Kelly, David; Buckman, Jim; Forbes, Heather; et al.
Abstract : The main pond within the historic Royal Botanic Garden Edinburgh is an important component of urban blue-green infrastructure. This paper reports on flood resilience provided by the pond (simulated using the CityCAT hydrodynamic model), its water residence times (obtained using the Shetran hydrological model), and the ecology and biodiversity (vascular plants, bryophytes, aquatic invertebrates, phyto- and zooplankton, birds) of the pond and the adjacent area. The results show that the pond improves the flood resilience with at least a 27% reduction in the peak discharge during a 1 h, one in 100-year event. The area represents a biodiversity hot spot with a range of native taxa occurring among introduced plant species. The plankton community is dominated by diatoms, reflecting elevated levels of turbulence and a relatively short residence time, with an average value of 10 days. Analysis of macroinvertebrate community indicates a potential for water quality improvement. The results are discussed in relation to multiple societal benefits related to flood resilience, recreation, education, water quality, amenity and biodiversity value. The conclusions may prove particularly valuable for introducing practical measures in the water catchment, preventing waterlogging of the soil and ensuring an uninterrupted supply of public services. This article is part of the theme issue 'Urban flood resilience'.